2021
DOI: 10.1049/itr2.12073
|View full text |Cite
|
Sign up to set email alerts
|

Using spatio‐temporal deep learning for forecasting demand and supply‐demand gap in ride‐hailing system with anonymised spatial adjacency information

Abstract: To reduce passenger waiting time and driver search friction, ride-hailing companies need to accurately forecast spatio-temporal demand and supply-demand gap. However, due to spatio-temporal dependencies pertaining to demand and supply-demand gap in a ridehailing system, making accurate forecasts for both demand and supply-demand gap is a difficult task. Furthermore, due to confidentiality and privacy issues, ride-hailing data are sometimes released to the researchers by removing spatial adjacency information o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Jiang et al [24] used an SVM neural network to build a least squares support vector machine (LS-SVM) based on an online car-hailing travel demand prediction model, and through experiments they showed that the prediction results of the proposed prediction model method were better than those of other methods. Rahman et al [25] used a one-dimensional convolutional neural network (1D CNN) and zone-distributed independently recurrent neural network (IndRNN) to build a spatiotemporal deep learning structure, and tested it on real online car-hailing data; their network outperformed traditional time series models and machine learning models. In response to the analysis of the spatiotemporal correlation of the car-hailing data, Ke et al [26] combined the ConvLSTM model and the LSTM network to extract the spatiotemporal and temporal characteristics of the travel demand of the car-hailing, and finally verified its effectiveness through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [24] used an SVM neural network to build a least squares support vector machine (LS-SVM) based on an online car-hailing travel demand prediction model, and through experiments they showed that the prediction results of the proposed prediction model method were better than those of other methods. Rahman et al [25] used a one-dimensional convolutional neural network (1D CNN) and zone-distributed independently recurrent neural network (IndRNN) to build a spatiotemporal deep learning structure, and tested it on real online car-hailing data; their network outperformed traditional time series models and machine learning models. In response to the analysis of the spatiotemporal correlation of the car-hailing data, Ke et al [26] combined the ConvLSTM model and the LSTM network to extract the spatiotemporal and temporal characteristics of the travel demand of the car-hailing, and finally verified its effectiveness through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Online ride-hailing has become popular across the country and is an important means of transportation for people because online ride-hailing is more convenient and flexible than bus and metro for passengers. The travel demand prediction of online ride-hailing has great significance for the development of online ride-hailing [1][2][3][4]. Deep learning is a new research direction in the field of machine learning, which is now widely applied in the field of transportation.…”
Section: Introductionmentioning
confidence: 99%